Penegakan Hukum Terhadap Pelaku Tindak Pidana Penipuan Investasi Melalui Media Internet - Suardi Suardi; Muh. Nur Iksan; Patahillah Asba (Jurnal Litigasi Amsir, 2022)
This study aims to determine and analyze how the law applies to court decisions given to online fraud perpetrators. This research is normative. The data collection in this study was library research (literary analysis) and was supported by interviews (interviews) supporting data and qualitatively analyzed. This research was conducted in Sidrap Regency, precisely at the Sidrap District Court Office, by seeking information related to the issues discussed in this decision to facilitate discussion and completion of writing. This research was conducted using the method of interviews with Judges of the Sidrap District Court and a literature study using references relevant to the problems in the author's thesis. Therefore law enforcement regarding this fraud crime can still be accommodated by the Criminal Code and Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning information and electronic transactions. Furthermore, obstacles in law enforcement against criminal acts of fraud based on electronic transactions are still influenced by five factors: legal factors, law enforcement factors, facilities and facilities that support law enforcement, community factors and cultural factors.